Social Media Platforms and Their Role in Addressing Deviant Behaviors from the Perspective of University Youth - Hazim, Mina Harith (ALBAHITH ALALAMI, 2025)
Objectives: This study aims to explore social media platforms and their role in addressing deviant behaviors from the perspective of university youth. Methodology: Classified as descriptive research, the study relied on the survey method. The research population consisted of students of the College of Political Science at the University of Baghdad for the academic year 2024–2025. The sample comprised 10% of the population; 100 students, selected using simple random sampling. Results: The findings showed that the majority of respondents use social media extensively (96%), with a strong preference for video content, especially on Instagram. Influencers and well-known personalities were the most followed. Respondents indicated that awareness-raising content competes with both negative and positive content and is regularly followed by students. The study found that the most common deviant behavior youth seek to limit is cyberbullying in all its forms. Digital awareness campaigns, especially video-based ones, were identified as the most used in raising awareness. Real-life relatable content had the strongest influence on respondents. Moreover, 83% acknowledged the importance of digital awareness campaigns. Conclusion: Deviant behaviors can be addressed by focusing on making content purposeful, as awareness content has a significant impact on youth. The research highlights the interaction of youth with social media content that contributes to correcting certain behaviors. It indicates that if used purposefully, social media can be an effective guiding and awareness tool for reinforcing moral values and reducing behavioral risks such as addiction, aggression, and extremism.